2003
DOI: 10.1002/jobm.200390030
|View full text |Cite
|
Sign up to set email alerts
|

Xylanolytic complex from Aspergillus giganteus: production and characterization

Abstract: An Aspergillus giganteus strain was isolated as an excellent producer of xylanase associated with low levels of cellulase. Optimal xylanase production was obtained in liquid Vogel medium containing xylan as carbon source, pH 6.5 to 7.0, at 25 degrees C and under shaking at 120 rpm during 84 h. Among the several carbon sources tested, higher xylanase production was verified in xylan, xylose, sugar-cane bagasse, wheat bran and corn cob cultures, respectively. Optimal conditions for activity determination were 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
4
14
1
Order By: Relevance
“…Nevertheless, an evident activity decrease was observed above 60°C. These findings are in agreement with those reported by Shah and Madamwar [55] and Coelho and Carmona [16], who reported that the optimum temperature was 50°C and the optimum pH was 5.3 and 6.0, respectively, for Aspergillus foetidus and Aspergillus giganteus xylanases. According to Table 3, the optimum temperature and pH value of xylanases from Aspergillus species ranges from 42 to 55°C and 4.0 to 6.0, respectively.…”
Section: Sds-page and Mass Spectrometry Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, an evident activity decrease was observed above 60°C. These findings are in agreement with those reported by Shah and Madamwar [55] and Coelho and Carmona [16], who reported that the optimum temperature was 50°C and the optimum pH was 5.3 and 6.0, respectively, for Aspergillus foetidus and Aspergillus giganteus xylanases. According to Table 3, the optimum temperature and pH value of xylanases from Aspergillus species ranges from 42 to 55°C and 4.0 to 6.0, respectively.…”
Section: Sds-page and Mass Spectrometry Analysissupporting
confidence: 94%
“…The observed protective effect of L-cysteine could be related to the presence of a reducing Fig. 4 Effect of pH and temperature on xylanase activity from the culture filtrate ( ) and on the PXII-1 xylanase preparation ( ) The half-lives for several fungi xylanases at 50°C have been reported as 1 h for Aspergillus foetidus [55], 13 min for A. giganteus [16], and 4 h for A. awamori NRRL 3112 [42]. Concerning stability at 55°C, xylanase II purified from A. caespitosus was fully stable for up to 90 min [54].…”
Section: Xylanase Hydrolytic Profilementioning
confidence: 96%
“…These results are in accordance to with results obtained by Coelho and Carmona [34], which obtained xylanase production 43% higher under static conditions and it was observed that xylanase activities peaks in 5 and 3.5 days cultures under static and shaking conditions, respectively, with xylan as carbon source by A. giganteus. Seyis and Aksoz [35] reported that T. harzianum 1073 D3 produced the maximum level of xylanase after 13 days with xylan as the only carbon source, under static conditions.…”
Section: Time Course Of Enzyme Production Under Shaking and Static Cosupporting
confidence: 95%
“…Heck et al (2002) reported 5.19 U/mg protein for xylanase of a strain of Bacillus subtilis; Damaso et al (2002), using Thermomyces lanuginosus (IOC-4145), obtained 85 U/mg protein for the xylanase activity in a filtered culture. Coelho and Carmona (2003) reported 107.43 U/mg protein for xylanase, using A. giganteus. The specific activity of xylanase determined in our work was lower than the range cited in the literature; however, no cellulase activity was found in the fraction P-II, using cellulose microcrystalline Sigma 1% (w/v).…”
Section: Chromatographic Separation Of the Hydrolysis Productsmentioning
confidence: 99%